2021
DOI: 10.1111/neup.12742
|View full text |Cite
|
Sign up to set email alerts
|

Senile plaque calcification of the lamina circumvoluta medullaris in Alzheimer's disease

Abstract: Vascular calcification is a common phenomenon in the elderly, predominantly appearing in the basal ganglia and in the lamina circumvoluta medullaris of the hippocampus. Calcifications are not an inherent feature of Alzheimer's disease. On the other hand, a rare presenile type of dementia with symmetrical Fahr‐type calcifications and numerous neurofibrillary tangles without senile plaques has been described by Kosaka in 1994 and was termed “diffuse neurofibrillary tangles with calcification” (DNTC). We here rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…In the aged hippocampus, arteries, pre-capillaries and capillaries were calcified ( Peters et al, 2018 ). Similar calcification of hippocampal vessels has been reported in AD patients ( Wegiel et al, 2002 ; Schober et al, 2021 ). A recent study showed that the tunica media of arterioles in the globus pallidus is calcified in aged individuals, confirmed both histologically and on CT. Calcification of the vascular tree showed a distribution pattern, starting in the ventral striatopallidum spreading posterolaterally into the external half of the globus pallidus ( de Brouwer et al, 2021 ).…”
Section: Bone In the Brain—an Overview Of Cerebrovascular Calcificationssupporting
confidence: 84%
See 1 more Smart Citation
“…In the aged hippocampus, arteries, pre-capillaries and capillaries were calcified ( Peters et al, 2018 ). Similar calcification of hippocampal vessels has been reported in AD patients ( Wegiel et al, 2002 ; Schober et al, 2021 ). A recent study showed that the tunica media of arterioles in the globus pallidus is calcified in aged individuals, confirmed both histologically and on CT. Calcification of the vascular tree showed a distribution pattern, starting in the ventral striatopallidum spreading posterolaterally into the external half of the globus pallidus ( de Brouwer et al, 2021 ).…”
Section: Bone In the Brain—an Overview Of Cerebrovascular Calcificationssupporting
confidence: 84%
“…There is differential involvement of the vascular tree (artery, capillary), which might be dependent on the anatomical region and underlying disease. For example, previous histopathological studies detected arterial calcification in aged subjects and AD patients compared to capillary bed calcification in the globus pallidus in Down syndrome patients ( Wegiel et al, 2002 ; Schober et al, 2021 ).…”
Section: Bone In the Brain—an Overview Of Cerebrovascular Calcificationsmentioning
confidence: 99%
“…It is well known that calcification of blood vessels is associated with vascular ageing and atherosclerosis, adding further evidence that atherosclerosis might be an early event in Alzheimer's disease development. To our knowledge, a previous published case report also linked vessel calcification with Alzheimer's disease [29].…”
Section: Resultsmentioning
confidence: 99%
“…Recent investigations have brought to light a significant association between a hereditary variant of CAA, known as the Dutch type, and IAC [189] . Studies have revealed a connection between osteopontin (OPN), and the TGFβ1/phospho-SMAD2/3 signaling pathway in calcified arteries affected by hereditary CAA [190,191] . Interestingly, the researchers observed a correlation between the pro-calcific accumulation of collagen 1, OPN, and the activation of the pSMAD2/3 pathway with the severity of CAA.…”
Section: Co-occurrence Of Calcification and Amyloidmentioning
confidence: 99%